Comparative Study Of Alternative Settlements In Indonesia And Timor Leste - Ar Raidah, Salsabila Fakhriyyah (Faculty of Law, Universitas Negeri Semarang, 2021)
Alternative Dispute Resolution (ADR) is a procedure in community practice which then gets recognition in the eyes of the law to settle a case between two or more parties by way out of court in a formal manner (litigation). ADR is considered to have more advantages, including easy, cheap, and fast, so it is more efficient and effective than solving cases in court. This paper aims to examine the existence of ADR in legal practice in Indonesia with a comparative review of the state of Timor Leste. The results of this paper reveal that compared to Timor Leste which is still new, Indonesia has first implemented ADR practices within a formal legal framework. Timor Leste actually also uses the ADR scheme in its daily community practice, but its implementation takes into account the elements of custom and society rather than the legal norms.